Sphingolipid Long-Chain Base Phosphate Degradation Can Be a Rate-Limiting Step in Long-Chain Base Homeostasis - Lambour, Benjamin; Glenz, René; Forner, Carmen; Krischke, Markus; Mueller, Martin J.; Fekete, Agnes; Waller, Frank (Frontiers in Plant Science, 2022)
Sphingolipid long chain bases (LCBs) are building blocks for membrane-localized sphingolipids, and are involved in signal transduction pathways in plants. Elevated LCB levels are associated with the induction of programmed cell death and pathogen-derived toxin-induced cell death. Therefore, levels of free LCBs can determine survival of plant cells. To elucidate the contribution of metabolic pathways regulating high LCB levels, we applied the deuterium-labeled LCB D-erythro-Sphinganine-d7 (D7-d18:0), the first LCB in sphingolipid biosynthesis, to Arabidopsis leaves and quantified labeled LCBs, LCB phosphates (LCB-Ps) and 14 abundant ceramide (Cer) species over time. We show that LCB D7-d18:0 is rapidly converted into the LCBs d18:0P, t18:0, and t18:0P. Deuterium-labelled ceramides were less abundant, but increased over time, with the highest levels detected for Cer(d18:0/16:0), Cer(d18:0/24:0), Cer(t18:0/16:0) and Cer(t18:0/22:0). A more than 50-fold increase of LCB-P levels after leaf incubation in LCB D7-d18:0 indicated that degradation of LCBs via LCB-Ps is important, and we hypothesized that LCB-P degradation could be a rate-limiting step to reduce high levels of LCBs. To functionally test this hypothesis we constructed a transgenic line with dihydrosphingosine-1-phosphate lyase 1 (DPL1) under control of an inducible promotor. Higher expression of DPL1 significantly reduced elevated LCB-P and LCB levels induced by Fumonisin B1, and rendered plants more resistant against this fungal toxin. Taken together, we provide quantitative data on the contribution of major enzymatic pathways to reduce high LCB levels, which can trigger cell death. Specifically, we provide functional evidence that DPL1 can be a rate-limiting step in regulating high LCB levels.